Clarification of morphological distinction between Artemisia sichuanensis var. sichuanensis (Asteraceae, Anthemideae) and A. sichuanensis var. tomentosa, with reduction of A. erlangshanensis to the synonymy of the latter variety - Guo, Xin-Qiang; Wang, Long; Yang, Qin-Er (Phytotaxa, 2020)
Based on observations on both herbarium specimens (including type material) and living plants in the wild, we demonstrate that Artemisia sichuanensis var. sichuanensis (Asteraceae, Anthemideae) differs from A. sichuanensis var. tomentosa only by the leaves abaxially sparsely pubescent (vs. densely gray arachnoid tomentose). In addition, A. erlangshanensis is found to be identical with A. sichuanensis var. tomentosa, and is thus synonymized herein.